Factors Influencing the Choice of Building Materials and their Relationships to Human Health - MAKINDE, Olusola Oladapo; AKANGBE, Olabode Oludayo; MAKINDE, Olubukunmi Temitope (PT Batara Swastika Harati, 2024)
The significance of materials choice and their relationships to structural elements, the functionality of structure, aesthetic value, economic performance, and human health cannot be overemphasized in building development. This study carried out a critical review of the literature on several factors, including structural integrity, cost- effectiveness, aesthetic appeal, health considerations, and functional requirements, in the choice of materials for buildings and other structural developments. This study identified some building materials used to achieve structural stability and discourse sustainable and smart building materials. This study used primary data from physical observations and secondary data from relevant literature. This study observed that a well-designed and functional building enhances productivity, satisfaction, and overall user experience. The study also found that smart materials, such as programmable glass, self-healing concrete, and energy-generating facades, enhance functionality by incorporating features such as energy efficiency, improved thermal comfort, and interactive user experiences. The choice of construction materials is closely intertwined with the functionality of the structure, esthetic value, economic performance, and other factors. The study concludes that different materials possess specific properties that directly impact the performance, human health, and functionality of various building elements. The study recommends that in deciding on the choice of materials to be used for building development, hasty decisions should be avoided regarding buildings and the spaces that they occupy.